A necrotic stimulus is required to maximize matrix-mediated myogenesis in mice - Drew Kuraitis; Maria Grazia Berardinelli; Erik J. Suuronen; Antonio Musarò (The Company of Biologists, 2013)
SUMMARY Biomaterials that are similar to skeletal muscle extracellular matrix have been shown to augment regeneration in ischemic muscle. In this study, treatment with a collagen-based matrix stimulated molecular myogenesis in an mdx murine model of necrosis. Matrix-treated animals ran ≥40% further, demonstrating functional regeneration, and expressed increased levels of myogenic transcripts. By contrast, matrix treatment was unable to induce transcriptional or functional changes in an MLC/SOD1G93A atrophic mouse model. In vitro, satellite cells were cultured under standard conditions, on matrix, in the presence of myocyte debris (to simulate a necrotic-like environment) or with both matrix and necrotic stimuli. Exposure to both matrix and necrotic stimuli induced the greatest increases in mef2c, myf5, myoD and myogenin transcripts. Furthermore, conditioned medium collected from satellite cells cultured with both stimuli contained elevated levels of factors that modulate satellite cell activation and proliferation, such as FGF-2, HGF and SDF-1. Application of the conditioned medium to C2C12 myoblasts accelerated maturation, as demonstrated by increased mef2c, myf5 and myogenin transcripts and fusion indexes. In summary, the collagen matrix required a necrotic stimulus to enhance the maturation of satellite cells and their secretion of a myogenic cocktail. Considering that matrix treatment supports myogenesis only in in vivo models that exhibit necrosis, this study demonstrates that a necrotic environment is required to maximize matrix-mediated myogenesis.